Karah Kost: capstone - Kost, Karah, artist (Colorado State University. Libraries, 2022)
The artist's statement: I want my work to represent the things that I myself enjoy and find interesting. Everything to me is a learning experience and a way to expand my knowledge of the universe and all its many different types of processes. Therefore my art is constantly expanding in technique, size, and meaning. Some of my work is 2D, some of it is 3D, but a lot of it is a representation of the ways that I think, learn, and experience this life. Before coming to school I had no idea what I was doing or how I should be thinking about my art. Now I know that in the future my freelance art will most likely be representing the different aspects of ADHD and the chaotic and spiraling forms of thought processes that come along with it. My journey with art has always been a little hazardous and in the last few years I’ve really been working towards communicating more through that of simplicity versus chaos, because I realized through trial and error that even though I might be trying to communicate something chaotic I can still do that using simplicity and probably do it better. In the end I have struggled with ADHD my whole life but even so have always thought of it as my superpower and something that has and will continue to inspire and motivate a majority of my art for years to come. The work I am especially interested in is branding, such as personal branding, product branding, service branding… etc. And this is just one category of design I am passionate about. More than anything, I want to be able to get to know my clients and their companies as closely as I can in order to create and manifest exactly what it is that they’ve been envisioning and then take it one step further and do even more to exceed just their initial expectations. Communication is key, and it is my job to turn that communication from the verbal to the visual.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design